Development of learning cycle box media and strengthening entrepreneurship in Pakis, Magelang - Rochiyati Murniningsih; Faza Khusnu Sa'adah; Ega Aldanisa Apriliani; Titania Ayu Rizqia; Ashadi Sulthon; Zaki Zaki (Community Empowerment, 2022)
The prolonged Covid-19 pandemic demands online learning in all lines of education. However, the community faces economic limitations for purchasing internet packages and natural conditions with limited internet access. The learning cycle box media development activity was made to increase the attractiveness of the school-age population to return to learning. The method is carried out through observation, discussion, mentoring through learning cycle boxes, production practices and online marketing. The results achieved were an increase in the learning motivation of the school-age population, as evidenced by the enthusiasm of attendance during learning activities and the implementation of entrepreneurship strengthening activities in the Wiropati Hamlet community. The sustainability of the program is highly guaranteed, with the involvement of Sahabat Rumah Baca as the youth driving force in Wiropati Hamlet and PKK women.